Reconciling corruption with conservation triage: Should investments shift from the last best places? - Packer, Craig (PLoS Biol, 2018)
Considerable outside funding will be required to overcome the financial shortfalls faced by most of Africa’s protected areas. Given limited levels of external support, it will be essential to allocate these funds wisely. While most recent studies on conservation triage have recommended prioritizing reserves with the highest remaining conservation value (the “last best places”), such investments are complicated by the fact that these same reserves often attract the greatest revenues from ecotourism and thus the most attention from corrupt local governments. Alternatively, philanthropic organizations might achieve greater returns from investing in the management of neglected areas with lower current conservation value but with less financial leakage from corruption. We outline here how high levels of corruption could favor a strategy that shifts investments away from the last best places.